Disparities in economic development since the industrial revolution - Bairoch, Paul.; Lévy-Leboyer, Maurice (London : Macmillan, 1981)
This book assembles all the contributions to one of the four major themes of the 7th International Economic History Congress which took place in Edinburgh on 13-19 August 1978"--P.
"
Includes bibliographical references and index.
occ 17/01/2019
Loans
Keywords: Economic history; Economic development; Equality of states